2022
DOI: 10.3390/rs14143338
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Spectral-Channel Attention Network for Denoising on Hyperspectral Remote Sensing Image

Abstract: Hyperspectral images (HSIs) are frequently contaminated by different noises (Gaussian noise, stripe noise, deadline noise, impulse noise) in the acquisition process as a result of the observation environment and imaging system limitations, which makes image information lost and difficult to recover. In this paper, we adopt a 3D-based SSCA block neural network of U-Net architecture for remote sensing HSI denoising, named SSCANet (Spatial and Spectral-Channel Attention Network), which is mainly constructed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In addition, due to the continuity and universality of the distribution of hyperspectral objects, self-similarity is an inherent property of hyperspectral images, which has been widely used in many popular denoising methods. At present, the development trend of spectral denoising methods is to combine the spatial and spectral similarity of images to improve the quality of images [28,29]. In [30], the authors proposed a low-rank restoration method that combines spatial and spectral information for image denoising, which simultaneously embeds the TV regularization, nuclear norm, and L 1 norm (LRTV).…”
Section: Optimization-based Methodsmentioning
confidence: 99%
“…In addition, due to the continuity and universality of the distribution of hyperspectral objects, self-similarity is an inherent property of hyperspectral images, which has been widely used in many popular denoising methods. At present, the development trend of spectral denoising methods is to combine the spatial and spectral similarity of images to improve the quality of images [28,29]. In [30], the authors proposed a low-rank restoration method that combines spatial and spectral information for image denoising, which simultaneously embeds the TV regularization, nuclear norm, and L 1 norm (LRTV).…”
Section: Optimization-based Methodsmentioning
confidence: 99%
“…Some previous studies on remote sensing images using CNN have demonstrated differences in the weights of different bands of an image across various application scenarios. The utilization of attentional mechanisms allows for improved focus on these weights [44,45]. Given that various bands or polarization modes in remote sensing data may respond differently to changes in water level, the incorporation of these attention mechanisms into the models could be a valuable addition.…”
Section: Model Architecturementioning
confidence: 99%
“…Yulong Guo et al [16] presented a sparse representation-based denoising method for water color hyperspectral data, adeptly separating signal from noise. Hongxia Dou et al [17] utilized a 3D U-Net architecture with SSCA modules, taking into account both spatial and spectral features of hyperspectral images to enhance denoising performance.Lintao Han [18] introduced the RSIDNet deep learning network, which bolsters denoising capabilities through multi-scale feature extraction and attention mechanisms. Masoud Moradi [19] determined the optimal wavelet functions for ocean color time series data.…”
Section: Introductionmentioning
confidence: 99%